Konsep Min Al-Ma'lu Ila al-Majhul Menurut Ibn Sina - Akhmad Rofii Dimyati (Menara Tebuireng, 2017)
One of the outstanding of Ibn Si>na>â€™s philosophy is the concept â€œmin al-maâ€™lu>m ila> al-majhu>lâ€. It is a scientific journey of â€œfrom the known into the unknownâ€. This is certainly confusing for common people. In short, Ibn Si>na> argues that the scientific journey has started â€˜from the knownâ€™ (identified) description and processed into broad and â€˜unidentified descriptionâ€™ since it deals with the true sincerity. The fist is called as being perceived in the mind, while the later is called as description resulted from outside of the mind. In other word, â€˜the known is everything existed in our mind. While the â€˜unknownâ€™ is everything must be found, investigated observed and so on. It is because all the process of attaining knowledge which are â€˜unknownâ€™ (majhu>l) inherent in the mind. It can be simply understood by anybody by elaborating it in detail and easily